Toll-Like Receptor 4 Activation Prevents Rat Cardiac Fibroblast Death Induced by Simulated Ischemia/Reperfusion - Parra-Flores, Pablo; Espitia-Corredor, Jenaro; Espinoza-Pérez, Claudio; Queirolo, Cristian; Ayala, Pedro; Brüggendieck, Francisca; Salas-Hernández, Aimee; Pardo-Jiménez, Viviana; Díaz-Araya, Guillermo (Frontiers in Cardiovascular Medicine, 2021)
Death of cardiac fibroblasts (CFs) by ischemia/reperfusion (I/R) has major implications for cardiac wound healing. In in vivo models of myocardial infarction, toll-like receptor 4 (TLR4) activation has been reported as a cardioprotector; however, it remains unknown whether TLR4 activation can prevent CF death triggered by simulated I/R (sI/R). In this study, we analyzed TLR4 activation in neonate CFs exposed to an in vitro model of sI/R and explored the participation of the pro-survival kinases Akt and ERK1/2. Simulated ischemia was performed in a free oxygen chamber in an ischemic medium, whereas reperfusion was carried out in normal culture conditions. Cell viability was analyzed by trypan blue exclusion and the MTT assay. Necrotic and apoptotic cell populations were evaluated by flow cytometry. Protein levels of phosphorylated forms of Akt and ERK1/2 were analyzed by Western blot. We showed that sI/R triggers CF death by necrosis and apoptosis. In CFs exposed only to simulated ischemia or only to sI/R, blockade of the TLR4 with TAK-242 further reduced cell viability and the activation of Akt and ERK1/2. Preconditioning with lipopolysaccharide (LPS) or treatment with LPS in ischemia or reperfusion was not protective. However, LPS incubation during both ischemia and reperfusion periods prevented CF viability loss induced by sI/R. Furthermore, LPS treatment reduced the sub-G1 population, but not necrosis of CFs exposed to sI/R. On the other hand, the protective effects exhibited by LPS were abolished when TLR4 was blocked and Akt and ERK1/2 were inhibited. In conclusion, our results suggest that TLR4 activation protects CFs from apoptosis induced by sI/R through the activation of Akt and ERK1/2 signaling pathways.